Local Experimentation with International Implications: The Powerful Contributions of Laboratoire Lausannois Lesson Study (3LS) - Lewis, Catherine (Formation et pratiques d’enseignement en question, 2026)
In the region surrounding Lausanne, centuries of thoughtful experimentation and ongoing careful observation have produced chocolate, cheese, and wine that are famous around the world. In just a little more than 10 years, the Lausanne Lesson Study Laboratory (3LS) has built a body of knowledge about Lesson Study that is equally remarkable. Readers have a treat in store.